Pengaruh Kompetensi terhadap Kinerja Pegawai melalui Kompensasi Sebagai Variabel Moderasi dalam Pelayanan Ekspor dan Impor - Wanda Ginanjar Kartasasmita; Anita Maharani; Mery Noviyanti (Ridwan Institute, 2021)
This study aims to analyze the effect of competence and compensation on employee performance, as well as to analyze moderate compensation between competence and employee performance. This type of quantitative research uses a case study method, a population of 102 employees with a total sampling technique so that the sample size is 102 employees. Data processing techniques using smart PLS. Research has shown that competence has an impact on employee performance. Employee performance can also be influenced by compensation and compensation can moderate competence with employee performance, performance can be supported by good compensation, it will improve performance.